Fisheries governance in the 21 st century: barriers and opportunities in South American large rivers - Baigún, Claudio Rafael M. (2016)
South American large-river fisheries are experiencing a growing pressure due to mining activity, construction of dams, water diversion, dredging, commercial overfishing, pollution, floodplain deterioration, agriculture, and development. Despite the fact that artisanal fisheries represent a valuable resource for many riverine communities and play a critical role in assuring food security and poverty alleviation, managers are challenged to develop sound governance processes that ensure the sustainability of resources and fishing communities. The lack of effective governanceprocesses in artisanal fluvial fisheries is rooted in several social, economic, institutional, and ecological/environmental constraints. Most large-river fisheries are managed under a conventional approach, applying centralized government control policies that minimize stakeholders? participation in management decision making. River-fisheries governance is dependent on institutions, policies, and economic and political scenarios that are outside the fishery sector. Market demands and constructionof dams and river fragmentation, mining, pollution, cattle agriculture, deforestation, and recreational fishing pressure are all factors that have the potential to alter fisheries sustainability. Governance mechanisms in South American large rivers can be developed at three levels but need to prioritize economic growth, food security, employment, equitable access to resources, and poverty alleviation and promote and integrate the sustainable use of fluvial resources through stakeholders´ involvement in decision-making processes. To achieve such goals, new institutional and legal arrangements should be promoted envisioning small-scale fisheries as ecosystem services and implementing an ecosystem-based approach that integrates ecological and human components to support better governance processes.